Opening up to the world through the translation of children’s songs - Medina Casanovas, Núria (Historia y Memoria de la Educación, 2016)
This article begins by examining the role of that children’s choirs played in the realm of non-formal educational institutions and what they represented in Catalonia. We then describe the treatment of music as a subject in the schools of primary education in our country. Finally, we focus on the importance of children’s songs being translated and and what this implies for the enrichment of the language and culture as well as the incorporation of new traditions and vocabulary.. The article also explains the methodology used for the translation of children’s songs and gives two translations from English into Catalan that belong to the repertoire of the Catalan children’s choirs.